Immunohistochemical Expression of Programmed Death Ligand 1 in Oral Extranodal Diffuse Large B Cell Lymphoma - Said, Rania Hanafi Mahmoud; Hussein, Fatma F.; El-Deeb, Amal M. (European Journal of Dentistry, 2022)
Objective Lymphomas are the third most common cancer after squamous cell carcinoma and salivary gland tumors. Extranodal diffuse B cell lymphoma (DBCL) represents 30 to 58% of non-Hodgkin's lymphoma. One of the major problems of DBCL is the high likelihood of disease relapse following treatment. A recent trend in the treatment of diffuse large B cell lymphoma (DLBCL) is blockage of an immune checkpoint inhibitor that targets the programmed death of cell ligand 1 receptors (PD-L1). PD-L1 activation results in negative regulatory signals that induce apoptosis and inhibit tumor antigen-specific T cells allowing immune evasion of the tumor.The aim of this aim is to measure the expression level of PD-L1 on oral tissue samples from DLBCL patients using immunohistochemistry.Materials and Methods This current study was performed at the Faculty of Dentistry, Tanta University, Egypt. Ethical approval was conducted from Faculty of Dentistry, Tanta University. Tissue samples were collected from 13 patients diagnosed with oral extranodal DLBCL) nongerminal center B cell like subtype. Both hematoxylin and eosin and immunohistochemical staining (The avidin-biotin-complex procedure) was performed with anti-PD-L1 antibody (clone number: 28–8, Abcam, Cambridge, Massachusetts, United States).Cytoplasmic and/or membranous positive intensity was graded as follows: very mild staining, mild staining, moderate staining, and intense staining using Image J, 1.41a (National Institutes of Health, United States) image analysis software. The mean area fraction of the stained cells was calculated by counting immunostained cells in three fields of each case by two pathologists. Data was entered in SPSS program for analysis.Results PD-L1 was overexpressed on tumor cells of oral extranodal DLBCL than control cells from lesion free areas of oral tissues of the same patient.
Keywords: oral extranodal diffuse B cell lymphoma; diffuse large B cell lymphoma; programmed cell death ligand 1